TINGKAT PELAYANAN SELASAR PEJALAN KAKI DI PASAR KAHAYAN PALANGKARAYA - Laufried Laufried; H. Hudan Rahmani (Jurnal Transportasi, 2013)
Pedestrians have a weak position when mixed with vehicular traffic . Therefore, it required facilities for pedestrians , which can be a pedestrian corridor. In reality, it is often found that the pedestrian corridors are improperly used, when the carridor is used for trading places resulting reduced spaces for pedestrians. All of these in turn reduces the level of service for pedestrians. This study was conducted in the market area of Jalan Kahayan, Cilik Riwut, in the City of Palangkaraya. Observations were made at the peak and at the normal time. The level of service is measured based on the concept of Level of Service described in the US Highway Capacity Manual 1994. The results of this study are expected to be used as a reference material for designing pedestrian facilities which are not at present available in the Indonesian Highway Capacity Manual . The results indicate that the level of service in the pedestrian corridor of Pasar Kahayan is D in peak condition, C in normal conditions, and D in a combined time conditions .